Non-Line-of-Sight Target Tracking With a Single Time Multiplexed Channel - Xianmin Zheng; Tailin Li; Ke Ding; Yihan Luo (IEEE Photonics Journal)
Here we propose a non-line-of-sight (NLOS) tracking scheme using only one single-pixel single-photon channel. It is demonstrated that sending multiple beams with proper time delay enables multiplexing of multi-echoes of the hidden object in the single channel. Based on the multiplexed temporal histograms, we achieve a retrieval of the object's position with centimeter precision. The experiment of following the target's linear motion is also performed, proving that our technique can reliably track the moving object. This time multiplexing-based NLOS tracking scheme provides a simple way to reduce the numbers of the detecting channels, which may contribute to low-cost NLOS applications.